Evidence‐informed implementation of nurse prescribing under supervision: An integrative review. (3rd September 2021) - Fox, Amanda; Joseph, Ria; Cardiff, Lynda; Thoms, Debra; Yates, Patsy; Nissen, Lisa; Chan, Raymond Javan
Abstract: Aim: To explore evidence reporting facilitators and barriers to implementation of nurse prescribing and provide practical recommendations for evidence‐informed implementation and adoption of nurse prescribing under a supervision model. Background: As demand for access to quality health care services increases, health professional roles are expanding to meet population needs. Nurse prescribing has been effective in some countries and is being considered globally to address growing health care demand. Successful implementation of health service models requires careful planning and consideration. No existing reviews have examined implementation factors in the literature. Design: Integrative review. Data sources: CINAHL, MEDLINE, PubMed and EMBASE databases were searched from inception to 15 April 2020. Review methods: This integrative review is guided by Whittemore and Knafl and adheres to PRISMA reporting guidelines. The sustainability of innovation framework was used to synthesize data concerning implementation and sustainability factors (i.e. innovation, organizational, political, workforce and financial) for nurse prescribing. Results: A total of 39 articles were reviewed with literature predominantly reporting findings related to non‐medical and nurse prescribing under various models. Variable evidence was found to inform nurse prescribing across five implementation and sustainability factors identifying several areas that require in‐depth consideration. Very little evidence is available on nurse prescribing under supervision. Conclusion: Introduction of service reform is often costly. This review highlights gaps in the literature and raises areas for consideration prior to implementation of this new service delivery model. The introduction of nurse prescribing must be planned and informed by available evidence to support effective adoption, practice and patient outcomes. Impact: There are significant gaps in evidence related to nurse prescribing under a supervision model. Based on the evidence synthesized in this review, this paper provides practical recommendations for health service providers, managers, clinicians, educators and researchers to support implementation and adoption of nurse prescribing.